The role of Parents on the Personality of Children - Zubaidah Zubaidah; Nur Hasanah Harahap; Erna Rahmawati Hatijah; Siti Sariyati; Nurwahidah Marliana (Edumaspul: Jurnal Pendidikan, 2023)
The family is a place to accommodate the first education for children where family teachings will be the main factor for the child to develop his behavior. Not only the development of behavior, the family is also the first place for children to carry out overall growth and development. So that the family has a big role during the physical formation and personality of the child, because both the personality and the strong physique of the child are factored in by the family environment and also by both great parents. Personality is a quality that is different from other people and is reflected in behavior. This is closely related to the title of this research which in the research method carried out, the author took several reading sources such as books, journals, and also other publications or can be called the literature study method. The purpose of using this Library study method is to help writers get information from various sources. So, from this method it turns out that the family plays a very important role in the development of the personality of the baby, because the good and bad personality of the baby depends on how the family and both parents educate their children. Keywords: Influence, Family, Personality,The family is a place to accommodate the first education for children where family teachings will be the main factor for the child to develop his behavior. Not only the development of behavior, the family is also the first place for children to carry out overall growth and development. So that the family has a big role during the physical formation and personality of the child, because both the personality and the strong physique of the child are factored in by the family environment and also by both great parents. Personality is a quality that is different from other people and is reflected in behavior. This is closely related to the title of this research which in the research method carried out, the author took several reading sources such as books, journals, and also other publications or can be called the literature study method. The purpose of using this Library study method is to help writers get information from various sources. So, from this method it turns out that the family plays a very important role in the development of the personality of the baby, because the good and bad personality of the baby depends on how the family and both parents educate their children.Keywords: Influence, Family, Personality,